A new species of Phyllagathis (Melastomataceae, Sonerileae) from Guangxi, China - Su, Yu-Lan; Liu, Yan; Liu, Ying (Phytotaxa, 2021)
Phyllagathis impressinervia (Melastomataceae, Sonerileae), a new species from northwestern Guangxi, China and previously misidentified as P. cavaleriei in Chinese herbaria, is illustrated and described. The new species closely resembles P. cavaleriei in leaf shape, inflorescence type, and morphology of stamens and capsule, but can be easily distinguished by the leaf veins strongly sunken adaxially, hypanthium pubescent with ca. 1 mm long, spreading glandular hairs, creamy white anthers, and conspicuous ovary crown at anthesis.